Lipidopathy disrupts peripheral and central amyloid clearance in Alzheimer's disease: Where are our knowledge - Shahram Darabi; Enam Alhagh Charkhat Gorgich; Fatemeh Moradi; Auob Rustamzadeh (IBRO Neuroscience Reports)
Amyloid-beta (Aβ) production is a normal physiological process, essential for neuronal function. However, an imbalance in Aβ production and clearance is the central pathological feature of Alzheimer’s disease (AD), leading to the accumulation of Aβ plaques in the brain. Low-density lipoprotein receptor-related protein 1 (LRP1) plays a critical role in both the central clearance of Aβ from the brain and its peripheral transport to visceral organs. Disruptions in these processes contribute to the accumulation of Aβ in the central nervous system (CNS) and the progression of AD. Recent research emphasizes the need for a broader focus on the systemic effects of organs outside the brain, particularly in the context of AD prevention and treatment. The contribution of peripheral systems, such as the liver, in Aβ clearance, is vital, given that Aβ levels in the plasma correlate closely with those in the brain. Consequently, targeting systemic processes, rather than focusing solely on the CNS, may offer promising therapeutic approaches. Furthermore, high-density lipoprotein (HDL) facilitates the formation of lipoprotein-amyloid complexes, which are important for Aβ transport and clearance, using proteins such as apolipoproteins E and J (ApoE and ApoJ) to form complexes that help manage Aβ accumulation. On the other hand, low-density lipoprotein (LDL) facilitates Aβ efflux from the brain by binding to LRP1, promoting its clearance. Given the relationship between lipid profiles and Aβ levels, along with lipid-modifying drugs, may be effective in managing Aβ accumulation and mitigating AD progression.